Master's Level Study in Education : a Guide to Success for Pgce Students. - Denby, Neil (McGraw-Hill International (UK) Ltd., 2008)
Designed to lead the student through the process of studying, writing and achieving at Master's level, this title intends to demystify the process by tackling those issues students find difficult. It is based on practical guidance and takes a commonsense approach to studying and writing at this level.